2019
DOI: 10.1055/s-0039-1697726
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Occluding Characteristics of Nanosized Eggshell/Titanium Dioxide with or without Saliva

Abstract: Objectives The study reports on the effectiveness of a ball-milled nanosized titanium dioxide composite (EB@TiO2) for DH management in comparison with commercial desensitizing paste with and without saliva. Materials and Methods  Forty-nine dentine specimens were prepared from extracted bovine anterior teeth. Twenty-one of the specimens were brushed with three desensitizing toothpaste for 7 days, namely: Group 1; EB@TiO2, Group 2; Colgate Pro-relief; and Group 3; Sensodyne repair (n = 7). Twenty-four specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…With TNPsESTP, the presence of TNPs could also have accounted for dentinal tubules’ occlusion. The results of this study are in agreement with those obtained by Onwubu et al 32 33 34 In one of Onwubu et al’s studies, 32 a slurry of both ESP with or without TNPs was used. The slurry was prepared by mixing 1g of powder with 40 mL of deionized water.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…With TNPsESTP, the presence of TNPs could also have accounted for dentinal tubules’ occlusion. The results of this study are in agreement with those obtained by Onwubu et al 32 33 34 In one of Onwubu et al’s studies, 32 a slurry of both ESP with or without TNPs was used. The slurry was prepared by mixing 1g of powder with 40 mL of deionized water.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in Onwubu et al's studies, bovine incisors were used; however, in the present study, human extracted molar teeth were used. [32][33][34] With Biorepair, the active ingredient, responsible for occlusion of dentinal tubule and dentin remineralization, is nanohydroxyapatite. The presence of hydroxyapatite in a nanoscale enhances its rapid dissolution and hence early occlusion of dentinal tubules.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The REFIX-containing toothpaste could also remineralize the dentin tissue effectively by depositing a mineral layer, thus progressively occluding the dentinal tubules. Depositing phosphate and calcium ions at the surface of exposed tubules forms a protective layer against dentinal hypersensitivity, 28 which is an effective treatment. 29 A clinical trial that evaluated the effectiveness of the REFIX-based toothpaste in 53 participants found that the participants experienced a significant reduction in dentin hypersensitivity after 1 week of use.…”
Section: Discussionmentioning
confidence: 99%
“…The results are in agreement with Surmeneva et al (19) , they found that nano-HA promote preferential remineralization of the outer layer of enamel caries lesion and full remineralization does not occur. This indicates that nano-hydroxyapatite reveal a completely cure in remineralization of early enamel lesions (20) .…”
Section: Discussionmentioning
confidence: 85%